‘Calabar está onde não está’: história, memória e mito (1869-2017) - Cavalcante, Marília Teles (2018)
‘Calbar is where he is not’ is a symbolic condition reflected in his "absent presence" in the discussions about his desertion be deemed as betrayal or not, a historical controversy of centuries. In order to answer it, historical productions were made, remembrances and celebrations, which are the sources for the development of this research. Starting from Calabar's basis as a myth, the goal is to indicate which interests are involved in each context and also what our mythical figure allows us to comprehend about each of them. The plot allows us to observe the relations between history, memory and myth, from the end of the XIX century until the year of 2017, in an effort to present sources and conclusions, from several contexts, and, through memory’s history accompany the evocation processes of the mythical figure of Calabar. Divided into three parts, we analyze the production of the Historical Institute of Alagoas on its regard, the 'new sources presented', the revisionisms and disputes about his attitude, perceiving how his image is being constructed in history; then, we follow the construction of his memory in Porto Calvo, AL, his native city, observing how they take ownership on his history, aiming to draw a 'cultural tourism', and how they seek to cause an identification with Calabar among the population. Finally, we observed the significant celebration of the 'Bicentennial of the Emancipation of Alagoas' occurred in 2017, aiming on the developed activities that resumed Calabar, in the cities of Porto Calvo and Maceió. Concluding the permanence of Calabar as a myth, presenting at what point from the complaint (traitor or hero) we are and what it allows us to reflect on the construction of Alagoas identity nowadays.